The Correlation Between Self Efficacy and Nurse’s Motivation with The Implementation of Nursing Care in Patient Wards in Islamic Hospital Purwokerto - Rere Pirda Tria Amanda; Etlidawati Etlidawati (Proceedings Series on Health & Medical Sciences, 2024)
Background: Self-efficacy and motivation are needed by a nurse in carrying out the nursing care process. Nurseswho have good self-efficacy and motivation will also produce good nursing care processes so that they will bebetter able to provide maximum nursing care services to patients. Method: This research uses a correlational analytical design with a cross-sectional approach. Sampling was taken using a total sampling technique of 45 respondents. The test used is the Spearman's rank correlation test. Results: Most of the respondents, 27 respondents (60.0%), were under 30 years old, and34 respondents (75.6%) were female. Most of the respondents, 40 respondents (88.9%), had Diploma 3 education, and 32 respondents (71.1%) had worked less than 5 years.29 respondents (64.4%) had good self-efficacy, 18 respondents (40.0%) had good motivation, and 29 respondents (64.4%) conducted completenursing care.Spearman's Rankcorrelation testbetween self-efficacyand theimplementation ofnursing careinthe inpatient room of Purwokerto Islamic Hospital indicated a p-value of 0.000 (0.05) with Spearman's correlationor rho of 0.840. The correlation between nurse motivation and the implementation of nursing care in the inpatientward of Purwokerto Islamic Hospital showed a p-value of 0.000 (0.05) with Spearman's correlation or rho of 0.762. Conclusion:There is a significant correlation between self-efficacy and the motivation of nurses with theimplementation of nursing care in the inpatient ward at Purwokerto Islamic Hospital.